New bioactive compounds from aquatic endophyte Chaetomium globosum. Issue 9 (3rd May 2018) - Ruan, Bao-Hui; Yu, Ze-Fen; Yang, Xue-Qiong; Yang, Ya-Bin; Hu, Ming; Zhang, Zhuo-Xi; Zhou, Qing-Yan; Zhou, Hao; Ding, Zhong-Tao
Abstract: Two new oxidation products-related aureonitol and cytochalasan were isolated from Chaetomium globosum fermented in Chinese yam ( Dioscorea opposita ) and determined as 10, 11-dihydroxyl- aureonitol (1 ) and yamchaetoglobosin A (2 ). Compound2 indicated significant inhibitory effect on nitric oxide production in LPS-activated macrophages, anti-acetylcholinesterase activity with the inhibition ratios of 92.5, 38.2% at 50 μM, and cytotoxicity to HL-60, A-549, SMMC-7721, MCF-7 and SW480 with the range of inhibition ratio at 51–96% for a concentration of 40 μM. Compounds1, 2 showed weak anticoagulant activity with PT at 16.8 s. Few work was reported on the anti-acetylcholinesterase, and anticoagulant activities of aureonitol, and cytochalasan derivatives. The preliminary structure–activity relationship stated that the oxidation ring-opening in yamchaetoglobosin A can retain the inhibitory effect against NO production and tumor cell. Abstract :